Balance Between Deformation and Seismic Energy Release: The Dec 2018 ‘Double-Dike’ Intrusion at Mt. Etna - Bonaccorso, Alessandro; Giampiccolo, Elisabetta (Frontiers in Earth Science, 2020)
We investigated the relation between the surface deformation and seismicity caused by dike propagation. In a previous study, Bonaccorso et al. (2017) found a simple but effective equation that relates the average thickness and dimension of the dike with the expected released mechanical energy and, therefore, to the seismic moment. In the early morning of 24 December 2018, the shallow portion of Etna volcano was suddenly crossed by a violent dike intrusion that, after few hours, reached the summit area and opened an eruptive fissure feeding a lava flow. The intrusion was accompanied by an intense seismic swarm, with hypocenter located beneath the summit craters and along the eruptive fracture, and by ground deformation inferring a tensile source of the eruptive dike. The seismicity also continued the following day, with a deepening of the hypocenters up to 3 km b.s.l. as a response to the onset of a further deeper intrusion which sought to penetrate the volcano edifice without reaching the surface. This situation generated the fear of potentially critical consequences of feeding a more dangerous eruption in the medium-low flanks. In this study, we analyze the balance between deformation caused by the modeled dikes and the released seismic energy by following the above-mentioned approach. It proved very useful in the specific case of Etna volcano eruptions, resulting an effective tool to monitor the state of the intrusion of the magma, and to evaluate if this intrusion has enough energy to continue propagating or to sto